ANALISIS PENGARUH KEUNGGULAN RELATIF, KESESUAIAN PRODUK, KERUMITAN, KEMAMPUAN DIUJICOBAKAN DAN KEMAMPUAN DIAMATI TERHADAP PROSES ADOPSI INOVASI: (Studi Kasus pada Avail FC BIO Sanitary Pad di Daerah Istimewa Yogyakarta) - Uswatun Chasanah; Reni Setyaningsih (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2015)
This study examined the influence of the relative advantage, compatibility of products, complexity, triability and the observability to process adoption of innovation. This research using a sample of 100 respondents who use pads Avail FC BIO Sanitary Pad. The data collected by using purposive sampling. Result of the regression analysis showed that there was a simultaneous influence among variables of relative advantage, compatibility, complexity, triability and observability. And the partially influence is variable relative advantage, complexity, triability and observability against the process to adoption of innovation on Avail FC BIO Sanitary Pad.